Hi Tami! As you may be aware, the distributive property is a way to simplify an algebraic equation. The expression that needs to be simplified comes in the form x ( y + z ) -- which is "x times the sum of y and z." In your case, x = -5, y = b, and z = -4, so it's -5 times the sum of b and -4.
Using the distributive property, x ( y + z ) can be written as ( x * y ) + ( x * z ). You can then use arithmetic to simplify the result.
For example, if x = -3, y = 2, and z = -4k, then the expression -3(2-4k) could be written as ( -3 * 2 ) + ( -3 * -4k ), and this can be simplified to (-6) + (12k), or -6 + 12k.
What equation, in the form (x*y)+(x*z), would you get by substituting the values from your expression into x, y, and z? Next, how can you simplify the result?